Ionic Transfer Reactions with Cyclohexadiene-Based Surrogates - Walker, Johannes C. L.; Oestreich, Martin (Synlett, 2019)
A current research program in our laboratory is devoted to the development of cyclohexa-1,4-diene-based surrogates of difficult-to-handle compounds and their application in metal-free ionic transfer reactions. These investigations grew from our interest in silylium ion chemistry and consequently concentrated initially on surrogates of gaseous and explosive hydrosilanes such as Me3SiH and even monosilane (SiH4). Since then, we have expanded the concept to design surrogates of other species including H2, mineral acids (HI and HBr), and hydrocarbons (isobutane and isobutene). This Account summarizes our discoveries in this area to date, describing the challenges we faced along the way and how we combatted them.1 Introduction2 Transfer Hydrofunctionalization: Variation of the Electrofuge3 Transfer Hydrofunctionalization: Variation of the Nucleofuge4 Transfer Hydrohalogenation Using a Modified Surrogate5 Surrogate Synthesis6 Conclusion
Keywords: ionic transfer chemistry; main-group catalysis; metal-free; surrogates; Wheland intermediates